2016
DOI: 10.1021/acsnano.6b04643
|View full text |Cite
|
Sign up to set email alerts
|

Nanocarved MoS2–MoO2 Hybrids Fabricated Using in Situ Grown MoS2 as Nanomasks

Abstract: The morphology and hybridization of nanostructures are crucial to achieve properties for various applications. An in situ grown 3D MoS2 nano-mask has been adopted to control the morphology and hybridization of molybdenum compounds. The in situ generated MoS2 mask on MoO3 nanobelt surfaces allowed us to fabricate a 3D c-MoO2@MoS2 hybrid nanostructure, in which c-MoO2 is a carved MoO2 nanobelt with well distributed hole-pattern. The nano-masks have been controlled by adjusting the alignments of MoS2. The exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 40 publications
1
35
0
Order By: Relevance
“…According to the previous reports, the intense peaks at 184 and 324 cm −1 are corresponding to the typical J1 and J3 peaks of the 1T MoS 2 , which indicated that 1T MoS 2 was obtained in this study. Very small amount of MoO 3 in the as‐grown MoS 2 layer is also confirmed by their vibration at 820 and 958 cm −1 in the Raman spectra (Figure c) . It is important that the graphene scaffold remains intact during the MoS 2 growth process and preserves the mechanical and electronic integrity of the anode structure.…”
Section: Resultsmentioning
confidence: 68%
“…According to the previous reports, the intense peaks at 184 and 324 cm −1 are corresponding to the typical J1 and J3 peaks of the 1T MoS 2 , which indicated that 1T MoS 2 was obtained in this study. Very small amount of MoO 3 in the as‐grown MoS 2 layer is also confirmed by their vibration at 820 and 958 cm −1 in the Raman spectra (Figure c) . It is important that the graphene scaffold remains intact during the MoS 2 growth process and preserves the mechanical and electronic integrity of the anode structure.…”
Section: Resultsmentioning
confidence: 68%
“…The lattice fringes with a d ‐spacing of 0.62 nm in Figure g are assigned to the (002) lattice plane of hexagonal MoS 2 , indicating that the MoS 2 nanosheets are stacked along the c ‐axis, with more active edges exposed . Simultaneously, the (001) plane of hexagonal MoO 3 with a lattice spacing of 0.26 nm is observed in the MoS 2 @MoO 3 composites . Energy‐dispersive X‐ray analysis (EDXA) is conducted to estimate the chemical composition of the hybrid structures, revealing that the material is composed only of Mo, S, and O.…”
Section: Resultsmentioning
confidence: 99%
“…1.5 mm) purchased from Sigma-Aldrich was directly used as electrode materials (Supporting Information, Figure S1). As shown in Figure 1a,t he ordered layered structure of pristine MoS 2 leads to astrong (002) reflection at 14.388 8, [12] which is shifted to alower angle after discharging to 1.0 V. Theintensity of the diffraction peaks around 408 8 becomes much weaker than that of pristine MoS 2 ,which should be ascribed to the intercalation induced phase change. As shown in Figure 1a,t he ordered layered structure of pristine MoS 2 leads to astrong (002) reflection at 14.388 8, [12] which is shifted to alower angle after discharging to 1.0 V. Theintensity of the diffraction peaks around 408 8 becomes much weaker than that of pristine MoS 2 ,which should be ascribed to the intercalation induced phase change.…”
mentioning
confidence: 97%
“…Our first aim is to find out the lowest discharging cutoff voltage at which MoS 2 has already undergone conversion reaction but still preserves its layered crystalline structure.T othis end, we collected the powder X-ray diffraction (XRD) patterns ( Figure 1a)a nd SK -edge X-ray absorption spectroscopy (XAS,F igure 1b)o fMoS 2 electrodes discharged to different voltages at 0.05 Ag À1 .T oavoid air exposure during the XRD measurement, the cycled electrodes are sealed with Parafilm, which has little effect on the diffraction peaks of the active materials (Supporting Information, Figure S2). As shown in Figure 1a,t he ordered layered structure of pristine MoS 2 leads to astrong (002) reflection at 14.388 8, [12] which is shifted to alower angle after discharging to 1.0 V. Theintensity of the diffraction peaks around 408 8 becomes much weaker than that of pristine MoS 2 ,which should be ascribed to the intercalation induced phase change. [13] Additionally,n op eaks related to Li 2 Sa re observed in the corresponding XAS spectrum ( Figure 1b).…”
mentioning
confidence: 97%